TouchSlide – Um Aplicativo para Controle Compartilhado de Exibição de Mídia em Dispositivos Móveis - Gonçalves, Gerlan S. L.; Souza, Daniel F. L.; Castro, Angélica F. de (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2014: Anais Estendidos do XX Simpósio Brasileiro de Sistemas Multimídia e Web, 2014)
Recent research in mobile media sharing show the possibility to delivery multimedia content on mobile networks. This paper describe the TouchSlide, an Android based application for media content sharing with educational purpose. The authors present an application for improving student-professor interaction in a class environment. Students and professor share slide content and can interact whith presentation using mobile devices. Based in a client-server architecture, the professor controls media exhibition into student’s mobile devices.